Cultivating Canavalia ensiformis: Is Institutional Function Still Needed? - Andi Nuddin; Rian Adhi Putra; Irmayani Irmayani; Nuringsih Nuringsih; Muhammad Akhsan Akib (Hasanuddin University, 2019)
Several problems deal with Canavalia ensiformis cultivations. They are the low-price competitiveness, the absence of processing industries and appropriate agricultural technology controlled by the farmers, the absence of fostering of farmers, especially in terms of marketing and postharvest processing.Therefore, the study explore how the role and function of coordination in institutions is needed as a solution for developing Canavalia ensiformis cultivation? The research was conducted from March to August 2019, using the survey method. Data collection is done through an expert system / or practitioner approach. The data obtained were analyzed using the Interpretative Structural Modeling (ISM) method. The results show that the existing institutions have not understood their roles and functions in the development of Canavalia ensiformis cultivation. This is an indication of the weak coordination function. The weak function of coordination is a result of weak understanding of the visions, low institutional knowledge and conflict between institutions. The results of the ISM analysis show that there are two key strategic programs in developing the commodity of Canavalia ensiformis, namely human resource and marketing development. These two sub-elements are institutional indicators. Therefore strengthening institutional functions is still needed in the development of Canavalia ensiformis cultivation.